Folic acid–maltodextrin polymer coated magnetic graphene oxide as a NIR-responsive nano-drug delivery system for chemo-photothermal synergistic inhibition of tumor cells. Issue 18 (24th April 2023) - Gong, Tao; Wang, Xiaoyu; Zhu, Huirui; Wen, Chaochao; Ma, Qing; Li, Xiaoning; Li, Meining; Guo, Rui; Liang, Wenting
Abstract : A multifunctional nanocomposite, MGO-MDP-FA, was designed to be an efficient chemo-photothermal therapeutic platform with targeted drug delivery DOX, NIR triggered drug release, excellent stability and high photothermal conversion efficiency. Abstract : The combination of chemo-photothermal therapy with high efficiency and fewer side effects has a good application prospect in cancer treatment. It is of great significance to construct a nano-drug delivery system with cancer cell targeting, high drug loading and excellent photothermal conversion efficiency. Therefore, a novel nano-drug carrier MGO-MDP–FA was successfully constructed by coating folic acid-grafted maltodextrin polymers (MDP–FA) on the surface of Fe3 O4 -modified graphene oxide (MGO). The nano-drug carrier combined the cancer cell targeting of FA and the magnetic targeting of MGO. A large amount of anti-cancer drug doxorubicin (DOX) was loaded by π–π interaction, hydrogen bond interaction and hydrophobic interaction, with the maximum loading amount and loading capacity of 657.9 mg g −1 and 39.68 wt%, respectively. Based on the excellent photothermal conversion efficiency of MGO, MGO-MDP–FA showed good thermal ablation effect of tumor cells in vitro under NIR irradiation. In addition, MGO-MDP–FA@DOX showed excellent chemo-photothermal synergistic tumor inhibition in vitro (tumor cell killing rate reached 80%). In conclusion, the novel nano-drug delivery system MGO-MDP–FA constructed in this paper provides a promising nano-platform for chemo-photothermal synergistic treatment of cancer.